2016
DOI: 10.1090/proc/13417
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic bounds for special values of shifted convolution Dirichlet series

Abstract: In [15], Hoffstein and Hulse defined the shifted convolution series of two cusp forms by "shifting" the usual Rankin-Selberg convolution L-series by a parameter h. We use the theory of harmonic Maass forms to study the behavior in h-aspect of certain values of these series and prove a polynomial bound as h → ∞. Our method relies on a result of Mertens and Ono [22], who showed that these values are Fourier coefficients of mixed mock modular forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They are generalizations of the classical Rankin-Selberg convolutions [17], [20] which were used to bound the growth of the Fourier coefficients of cusp forms. Properties of these shifted convolution Dirichlet series have been investigated recently; it was first shown that these shifted convolution values are essentially coefficients of mixed mock modular forms (see [15]) and later the p-adic properties of these series (see [4]) and their asymptotic behavior (see [2]) were investigated. Initially motivated by a desire to compute these L-values and understand the explicit construction of the Weierstrass mock modular form (in terms of other known elliptic invariants), we offer a closed formula for these generating functions L f E (z).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are generalizations of the classical Rankin-Selberg convolutions [17], [20] which were used to bound the growth of the Fourier coefficients of cusp forms. Properties of these shifted convolution Dirichlet series have been investigated recently; it was first shown that these shifted convolution values are essentially coefficients of mixed mock modular forms (see [15]) and later the p-adic properties of these series (see [4]) and their asymptotic behavior (see [2]) were investigated. Initially motivated by a desire to compute these L-values and understand the explicit construction of the Weierstrass mock modular form (in terms of other known elliptic invariants), we offer a closed formula for these generating functions L f E (z).…”
Section: Introductionmentioning
confidence: 99%
“…They are generalizations of the classical Rankin-Selberg convolutions [17], [20] which were used to bound the growth of the Fourier coefficients of cusp forms. Properties of these shifted convolution Dirichlet series have been investigated recently; it was first shown that these shifted convolution values are essentially coefficients of mixed mock modular forms (see [15]) and later the p-adic properties of these series (see [4]) and their asymptotic behavior (see [2]) were investigated.…”
Section: Introductionmentioning
confidence: 99%